In search of rules for creative design process - Kristanti Dewi Paramita (Department of Architecture Faculty of Engineering Universitas Indonesia, 2024)
Architecture is driven by a set of rules which governs design actions and practices; which vary depending on the expected design objectives and intentions. The collection of articles in this ARSNET issue provides different perspectives that revisit the manifestation of rules in the design process. This edition highlights how rules do not only apply to form-making in the quest for beauty, nor it is limited to the social and cultural constraints that create a rather fixed and limited design manoeuvre. Through this issue's investigation of rules in design pedagogy and practice across contexts, some new objectives of rules in design are offered, demonstrating a more fluid and open manifestation of rules in the creative design process.